Proposed red team development and training workflow program for a Power Grid Company in the Philippines - Santos, Roma O. (Animo Repository, 2023)
This project is to develop a Red Team training workflow in Information Technology Cyber Security Operations Power Grid. Red Teaming is an advanced form of assessment that can be used to identify weaknesses in endpoints, networks, systems, applications, and perimeter. The purpose of this project is to assess and evaluate the various training of a Red Team for the security effectiveness together with Blue Team on improving Cyber Security Operations performance to strengthen Power Grid security posture. The design of the study includes ideas, research, and observation of current practices. The analysis yielded various dimensions of red team process effectiveness using tactics, techniques, and procedures (TTP) to emulate real-world threats and to train and measure the effectiveness of the people, processes, and technology used to defend Power Grid critical infrastructures. Keywords: endpoints, Red Team, Blue Team, Power Grid, assessment, perimeter